(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article scientifically investigates the tools and systemic qualities of consciousness in classical epistemology. The emerging non-classical epistemology seeks to explore the inner potential of the mind from a "new" perspective, abandoning ideas such as skepticism, fundamentalism, and subject-centralization, and explores issues that have escaped the attention of classical cognitive theory. It is also necessary to consider the application by postmodernism of the principles of a new approach to the process of cognition.